(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
The learning situation is influenced by various aspects of the learning environment, such as classroom discourse, tone of voice, and content. These factors influence student interaction, understanding, and motivation. Constructive criticism helps improve learning, while peer tutoring supports collaboration and knowledge sharing. This article examines how these elements shape the classroom experience and contribute to effective learning